2007
DOI: 10.1021/op700086d
|View full text |Cite
|
Sign up to set email alerts
|

Process Development of the Synthetic Route to R116301

Abstract: We describe in this paper the synthesis of compound 1 (R116301), which was developed to prepare pilot scale quantities (20-50 kg) of drug substance. The synthesis involves the s BuLi deprotonation of Boc-protected piperidone acetal 2, followed by benzaldehyde addition and ring closure to cyclic carbamate 4. Piperidine acetal 5 is resolved with Brown's acid and acylated. The ketone obtained after piperidine acetal deprotection undergoes reductive amination with N-benzyl piperazine, the most critical step in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The oxazolidinones 25 were formed with reasonable diastereoselectivity (dr 80:20) and good enantioselectivity (er 87:13 for major isomer, as determined by 1 H NMR spectroscopy with the Pirkle solvating agent). A similar (but racemic) procedure has been conducted on a 4‐substituted N ‐Boc‐piperidine as part of a synthesis of an NK 1 antagonist 18…”
Section: Resultsmentioning
confidence: 99%
“…The oxazolidinones 25 were formed with reasonable diastereoselectivity (dr 80:20) and good enantioselectivity (er 87:13 for major isomer, as determined by 1 H NMR spectroscopy with the Pirkle solvating agent). A similar (but racemic) procedure has been conducted on a 4‐substituted N ‐Boc‐piperidine as part of a synthesis of an NK 1 antagonist 18…”
Section: Resultsmentioning
confidence: 99%
“…A similar (but racemic) procedure has been conducted on a 4-substituted N-Boc-piperidine as part of a synthesis of an NK 1 antagonist. [18] In 2008, we reported that the organolithium derived from deprotonation of N-Boc-piperidine with sBuLi and TMEDA could be converted to its organozinc derivative and used in Negishi-type coupling reactions with aryl bromides to give 2-arylpiperidines. [19] To our disappointment, this procedure was unsuccessful using the DTR method.…”
Section: Full Papermentioning
confidence: 99%
“…This difficulty has been noted by others, and has unfortunately been the cause of abandonment of many Ti-based procedures for large scale applications. [17] When first scaling up the present reaction, the filtration required an unacceptable time (several hours to days) to complete, thus rendering the process impractical for large scale. Numerous variations of the aqueous solution used for quenching, order of addition, and filtration medium led to no improvement in filtration rate.…”
mentioning
confidence: 99%